Sergei Eisenstein as seen by Peter Greenaway: a dialectic representation of an (anti-)great film director - Chinita, Fátima (2019)
ABSTRACT - Peter Greenaway’s recent biopic of the great Russian film director and master of montage Sergei M. Eisenstein, Eisenstein in Guanajuato, forms an important addition to filmic life writing. Greenaway ‘writes’ Eisenstein on screen through the film director’s actions as documented across an array of sources—including Eisenstein’s own autobiography—but he also reveals Eisenstein’s inner thoughts and feelings, using Eisenstein’s own voice (that is, his theories and film practice). Rather than portraying the Russian director at work, Greenaway opted to present Eisenstein’s directorial film philosophy, attempting to capture the essence of being ‘Eisenstein’. The film focuses on fourteen crucial months in the director’s life: the period he spent in Mexico, from where he was banished without completing what could have been his directorial masterpiece, the film Que Viva Mexico! Greenaway is laudatory of Eisenstein’s importance for the history of cinema, whilst depicting him in carnivalesque and corporeally grotesque terms. Thus, Greenaway simultaneously portrays Eisenstein as a great man and an anti-hero, in truly dialectical form. These apparently contradictory images of the cinematic master, functioning as thesis and antithesis, build up into something larger: a synthetic Eisenstein. The result is a larger-than-life, entirely ecstatic Eisenstein and an ode to his synaesthetic and dialectical approach to life and cinema. In doing this, however, Greenaway doubles his subject’s ‘voice’ with his own and also ‘writes’ himself through Sergei Eisenstein’s theory and practice.